Editorial Preface: Urban Travel Behavior in the Middle East and North Africa - E. Masoumi, Houshmand (TeMA - Journal of Land Use, Mobility and Environment, 2018)
This Special Issue the TeMA. Journal of Land Use, Mobility and Environment focuses on an already researched subject of urban travel behavior and decisions in the less-studied geographical context of the Middle East and North Africa (MENA).